Серебряные монеты правителей античной Македонии в собрании Одесского археологического музея - Булатович, С.А. (Материалы по археологии Северного Причерноморья, 2009)
The article deals with the issue (18 items) of small group of silver royal coins of Ancient Macedonia from the collection of Odessa Archeological Museum: 4 coins of Alexander I, 1 coin of Philip II, 9 coins of Philip III Arrideus, 1 coin of Demetrius Poliorketes, 2 coins of Antigonus Gonatus and 1 coin of Philip V. The article also provides the information on findings of Macedonian coins in the Northern Black Sea Region.